Intercultural Pedagogical Practices and Promotion of Mental Health in Cofán Indigenous Schools (Praxis Educativa, 2026)
This study analyzes mental health promotion practices in Cofán schools in Valle del Guamuez, Putumayo, and their consistency with Laws 2383 of 2024 and 2460 of 2025. Using a qualitative approach based on documentary analysis and reflexive hermeneutics, it compares the Community Educational Project (PEC) and the Integrated and Intercultural Indigenous Educational Model (MEPII) with current regulations. The findings reveal common ground  regarding teachers’ role, community care, and the importance of territory, language, and spirituality. However, tensions emerge when the regulations’ technical approach overlooks rituals, knowledge holders’ participation, andcommunity-based assessment practices. The study concludes that Cofán pedagogy creates protective environments consistent with international standards. It recommends establishing coordination pathways among schools, health services, and Indigenous councils; strengthening culturally relevant teacher training; and developing indicators and  protocols in collaboration with traditional authorities.
Keywords: mental health; intercultural education; indigenous peoples; socio-emotional skills